Credibility and compliance: The EU's Common Foreign and Security Policy (CFSP) risks forfeiting its leverage in the Western Balkans - Solveig Richter; Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2008)
EU foreign ministers reiterated their support for the enlargement process at a meeting of the External Relations Council on 8 December 2008. The promise to accept the Western Balkan countries for membership in the European Union, once they have met the criteria, has been for a long time the most effective instrument of the CFSP in this conflict-burdened region. The Western Balkans are of particular relevance to the European Union: The CFSP was created and developed in the context of the European Union's attempt to transform the conflicts in this part of Europe. It is in this region where the European Union's resolve to achieve the status of a sovereign and equal actor in international affairs is permanently being tested
Keywords: 320